ANALISIS FAKTOR RISIKO TERHADAP KETERLAMBATAN PROYEK KONSTRUKSI THE HIMANA CONDOTEL - Ni Made Sintya Rani; Ni Kadek Sri Ebtha Yuni (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
One of the problems in construction activities is the risk of delays in the construction project. In The Himana Condotel project, several obstacles make some of the work not on the schedule. We analyze risk factors for delays to find out the dominan risk dan the solution. This research method uses a quantitative descriptive method and using questionnaires and interviews. The respondents were taken based on the criteria that are the respondent who has the important position at the Himana Condotel Project. From the data, we can specify the frequency and consequences occur risk that uses semantic differential scale in the questionnaire, that obtained the dominant risk factor based on the risk rating table with the highest risk level. After we get the dominant risk factors and the risk description, then we can determine the mitigation action that we can suggest. From the analysis, we get 5 variable risk factors for delay from The Himana Condotel project that is planning aspects, employment documents and contracts aspects, implementation aspects, resource aspects, and environmental aspects. Of the five aspects, the risk descriptions are described as 48. The dominant risk is obtained based on the percentage of the risk level, the risk level is obtained with a value of 36 %. From the five aspects of the risk factors for delays, all of them have high risks and 17 descriptions of risks that have a high-risk level. The suggested matters for the dominant risk mitigation to be carried out are more coordination between the parties involved, the preparation of schedule and planning in more detail, technical implementation in the fields especially for BQ, contract, work planning and terms to get more attention and increase the accuracy of the implementation of work as planned.